Efficacy of Nano Urea on Nitrogen Use Efficiency of Irrigated Maize under Temperate Ecology - , Barenya Gogoi, Raihana H Kanth, Tauseef Ahmad Bhat, Amal Saxena, Inayat M. Khan, Fehim J. Wani, Aijaz Nazir, Bisma Jan, Hadiya Kounsar, Bilkees Jamsheed, Khursheed Ahmad Dar, Jibinsha P T (Archives of Current Research International, 2024)
A field experiment was conducted during the Kharif-2022 season at the Agronomy Research Field, FOA, SKUAST-Kashmir, to investigate the efficacy of nano-urea in improving nitrogen-use efficiency in irrigated maize. Ten treatments were evaluated viz., T1: Control, T2: Recommended dose of Nitrogen (RDN) as basal (prilled urea), T3: 75% RDN + 1 spray nano-urea at 2 ml L-1 (60 DAS), T4: 75% RDN + 1 spray at 4 ml L-1 (60 DAS), T5: 50% RDN + 2 sprays at 2 ml L-1 (30 and 60 DAS), T6: 50% RDN + 2 sprays at 4 ml L-1 (30 and 60 DAS), T7: 25% RDN + 2 sprays at 6 ml L-1 (30 and 60 DAS), T8: 25% RDN + 2 sprays at 8 ml L-1 (30 and 60 DAS), T9: 25% RDN + 1 spray at 6 ml L-1 (60 DAS), T10: 25% RDN + 1 spray at 8 ml L-1 (60 DAS). The experiment was carried out following a randomized complete block design with three replications. Results revealed that treatment T6 (50% RDN as basal + 2 sprays at 30 and 60 DAS at 4 ml L-1 of nano-urea) exhibited superior performance compared to the recommended nitrogen dose (T2) and other treatments in enhancing nutri-ent-use efficiency. Notably, treatment T6 demonstrated the highest nitrogen uptake in grain (101.92 kg ha-1) as well as stover (67.41 kg ha-1), surpassing all other treatments. Additionally, agronomic efficiency was significantly higher in T8, while physiological efficiency peaked in T6. Yield attributes and overall yield showed consistent improvements in treatments receiving nano-urea. Furthermore, treatments utilizing nano-urea demonstrated higher net returns and benefit-cost ratios, with T6 particularly standing out. These findings underscore the potential of foliar application of nano-urea to halve the recommended dose of prilled urea, thereby enhancing nitrogen uptake, nutrient-use efficiency, yield, and economic returns, while promoting sustainability in agriculture.